Efficiency analysis of pond fish culture system in Negeri Kedah and Pulau Pinang: Data envelopment analysis approach - Samah, Rozana; Kamarudin, Roslina; Lim, Hock Eam (GSSRR, 2016)
Aquaculture is the solution to the issue of over-exploited for capture fisheries and demand of fish that growing faster.In addition, the available resources keep decreasing and there is a need to fully utilize the resource efficiently in order to achieve sustainable development of aquaculture. Thus, this study estimates the technical efficiency of pond fish culture system in Malaysia.This study employs Data Envelopment Analysis (DEA) approach to analyze the technical efficiency of 121 aquaculture farmer in the states of Kedah and Pulau Pinang and also investigates the determinants affecting the technical efficiency by employing Tobit regression model. The estimated result reveals a mean of technical efficiency was 0.76, which implies that the farmer’s efficiency could be further to the extent of 24% in term of output level.The estimated Tobit regression model reveals that the level of education, farm size and species cultured were the factors that significantly affect the level of technical efficiency.Thus, for the development of aquaculture, technical efficiency aspect should be emphasized.